Research Progress of Traditional Chinese Medicine in Regulating Tumor Associated Macrophages in Gastric Cancer - Lei, Xinyi; Jiang, Jing; Xiao, Gang; Tan, Raoyan; Wu, Yijing (Journal of Contemporary Medical Practice, 2025)
Gastric cancer (GC) is one of the multiple malignant tumors of the digestive tract. Most patients with gastric cancer have no obvious discomfort in the early stage, and once discovered, they are mostly in the middle and late stages, and the morbidity and mortality rate are increasing year by year. Its occurrence and development depend on a variety of mechanisms, among which tumor microenvironment (TME) and tumor-associated macrophages (TAMs) have attracted more and more attention. Tumor-associated macrophages affect the occurrence and development of tumors and are closely related to tumor prognosis by inducing apoptosis, promoting autophagy, promoting angiogenesis, and immune escape. In recent years, traditional Chinese medicine (TCM) has been widely studied and applied to the field of cancer, and it has been found that TCM mainly exerts its anti-gastric cancer effects by inhibiting the proliferation, metastasis and angiogenesis of cancer cells, promoting apoptosis of cancer cells, inducing autophagy of tumor cells, and immune function. As one of the effective treatment methods, traditional Chinese medicine can not only regulate TAMs to inhibit tumor growth, but also the active ingredients and targets may become a new research direction in the field of immunotherapy. Therefore , this review describes the tumor-associated macrophages and their roles in gastric cancer progression, and combs and summarizes the molecular targets and mechanisms of action of different kinds of TCM monomers, TCM combinations, and novel TCM preparations against gastric cancer, so as to provide a mechanistic references for the clinical treatment of gastric cancer with TCM, and to explore the potential of TCM in preventing gastric cancer and related diseases.